Meningkatkan Karakter Siswa dan Kearifan Lokal dengan Kurikulum Adaptif Berbasis Teknologi: Studi Kasus di SMP Al-Ikhlas, Astanajapura, Cirebon - Anwar, Ahmad Khoiril; Yono; Khumaedi, Akmad; Pramana, Rudi (Jurnal Studi Multidisiplin Qomaruna, 2025)
The rapid development of digital technology requires educational institutions to continuously adapt their curricula to remain relevant, while simultaneously preserving education’s fundamental role in character development and the preservation of local cultural values. In practice, however, many schools—including pesantren-based schools—still face challenges in meaningfully integrating technology without weakening character education and local wisdom. This study aims to develop and examine the implementation of a technology-based adaptive curriculum that effectively strengthens students’ character while integrating local wisdom. The research was conducted at SMP Al-Ikhlas, Astanajapura District, Cirebon Regency. This study employed a qualitative approach using a case study method. Data were collected through in-depth interviews, participatory observation, and document analysis. The findings indicate that a technology-based adaptive curriculum facilitates learning that aligns with students’ individual needs, interests, learning styles, and learning pace. The curriculum also provides opportunities for value-oriented and local wisdom–based projects and enables more holistic student assessment. Furthermore, technology plays a crucial role in providing interactive platforms and rich learning resources to internalize character values and promote local wisdom in a contextual manner. The implications of this study suggest that a technology-based adaptive curriculum offers both theoretical and practical guidance for curriculum developers, teachers, and policymakers in designing and implementing junior secondary education that is more relevant, adaptive, and rooted in noble cultural values.